Using the history of science to teach scientific inquiry - (:unkn) unknown (Scientific Methodical Center, 2016)
The aim of the research is to detect the views of the science teacher candidates about the nature of scientific inquiry before and after a history of science based teaching process. The research was made with the participation of 18 teacher candidates, who were enrolled in the primary science-teaching department of an Istanbul-based university. The qualitative data collection and analysis methods were used in the research, which was based upon the “case studies” to uncover the views in more details. Data of the research were collected by using the document analysis and interview. The data were assessed through the content and descriptive analysis methods. The results of the research represented that the teacher candidates’ views about the guidance of the scientific questions to the scientific investigations, the multiple purposes of the scientific investigations and the justification of the scientific knowledge were “weak” in the pre-test, and their views about the remaining aspects were at the level of “informed.” The teacher candidates could not express “sophisticated” views about any aspect. After the implementation process, it was seen that the teacher candidates’ views about the method diversity and the distinctions between the data and the evidence improved, but there was no difference in their views about other aspects. © 2016, Scientific Methodical Center. All rights reserved.
Keywords: History of science; Nature of scientific inquiry; Science teacher candidate; Science teaching